The CXCR4 antagonist POL5551 is equally effective as sirolimus in reducing neointima formation without impairing re-endothelialisation - Hamesch, Karim; Subramanian, Pallavi; Li, Xiaofeng; Dembowsky, Klaus; Chevalier, Eric; Weber, Christian; Schober, Andreas (Thrombosis and Haemostasis, 2012)
Impaired endothelial recovery after the implantation of drug-eluting stents is a major concern because of the increased risk for late stent thrombosis. The disruption of the chemokine axis CXCL12/CXCR4 inhibits neointima formation by blocking the recruitment of smooth muscle progenitor cells. To directly compare a CXCR4-targeting treatment strategy with drugs that are currently used for stent coating, we studied the effects of the CXCR4 antagonist POL5551 and the drug sirolimus on neointima formation. Apolipoprotein E-deficient mice were treated with POL5551 or sirolimus continuously for 28 days after a carotid wire injury. POL5551 inhibited neointima formation by 63% (for a dosage of 2 mg/kg/day) and by 70% (for a dosage of 20 mg/kg/day). In comparison, sirolimus reduced the neointimal area by 69%. In contrast to treatment with POL5551 during the first three days after injury, injection of POL5551 (20 mg/kg) once per day for 28 days diminished neointimal hyperplasia by 53%. An analysis of the cellular composition of the neointima showed a reduction in the relative smooth muscle cell (SMC) and macrophage content in mice that had been treated with a high dose of POL5551. In contrast, the diminished SMC content after sirolimus treatment was associated with a neointimal enrichment of macrophages. Furthermore, endothelial recovery was impaired by sirolimus, but not by POL5551. Therefore, the inhibition of CXCR4 by POL5551 is equally effective in preventing neointima formation as sirolimus, but POL5551 might be more beneficial because treatment with it results in a more stable lesion phenotype and because it does not impair re-endothelialisation.
Keywords: Restenosis; stents; vascular remodelling; chemokines